Antlions (Neuroptera, Myrmeleontidae) along the North Caspian shore; distributional analysis and zoogeographical division of Caspian coast of Russia - VICTOR A. KRIVOKHATSKY; Ilhama Kerimova; VASILYI V. ANIKIN; DMITRYI M. ASTAKHOV; ANNA S. ASTAKHOVA; ELENA V. ILYINA; IGOR S. PLOTNIKOV; JULIA V. SAMARTSEVA (Society for Indonesian Biodiversity, 2020)
Abstract. Krivokhatsky VA, Kerimova IG, Anikin VV, Astakhov DM, Astakhova AS, Ilyina EV, Plotnikov IS, Samartseva JV. 2020. Antlions (Neuroptera, Myrmeleontidae) along the North Caspian shore; distributional analysis and zoogeographical division of Caspian coast of Russia. Biodiversitas 21: 258-281. Zoogeographically regionalization of Northern Caspian territory, adjacent Eastern Caucasian and Volga-Ural regions were carried out by using the original cladistic program (CLA) based on faunistic investigations of Neuroptera, Myrmeleontidae. A total of 47 of elementary districts of physical geography or geobotanical mapping and 41 species of antlions were used for analyses in the Matrix. 46 elementary faunas were combined in the region into seven concrete faunas. The ConCaspian and Volga-Ural antlion faunas were mixed. Aspoeckiana uralensis Hölzel, 1969 was considered as superspecies with a complex of five subspecies with overlapping areas of distribution, associated in its origin with the spread of Northern antelopes (Saiga tatarica (Linnaeus, 1766), Gazella subgutturosa Guldenstaedt, 1780, Procapra gutturosa Pallas, 1777). At the North Caspian Shore Aspoeckiana uralensis uralensis Hölzel, 1969, and Aspoeckiana uralensis jakushenkoi Zakharenko, 1983, cohabited with the saiga antelope, using their paths for larval colonies. The dynamics of Macronemurus bilineatus Brauer, 1868 area over the past 100 years was described in detail. For some paleoenvironmental conditions of their origin and colonization of the Caspian region are reconstructed. The leading role of Turan in the formation of the fauna of the antlions is determined.